Q: What is the nth term out of 7 9 11 13 15?

Write your answer...

It is: 2n+9

The sequence is simply achieved by adding 2 to each value9+2=1111+2=1313+2=1515+2=1717+2=1919+2=21so the nth term can be calculatedThe value of the nth term = the value of (nth-1 term) +2.

2n + 1

The nth term is: 2n+7 and so the next number will be 19

The nth term in this sequence is 4n + 3.

If you mean: 15 11 7 3 then the nth term is 19-4n

The next term is: 15+4 = 19 The nth term is: 4n-5

If you mean -1 3 7 11 15 then the nth term is 4n-5 and so the next term will be 19

The nth term is 2n+5 and so the next number is 17

It is: nth term = 5-4n and so the next term will be -19

The nth term is 4n-1 and so the next term will be 19

1...2....3....43...7...11..157 - 3 = 411 - 7 = 415 - 11 = 4(the start of the nth term is 4n)4 x 1 = 4(but the first term is 3, so...)4 -1 = 3nth term = 4n - 1

The nth term for that arithmetic progression is 4n-1. Therefore the next term (the fifth) in the sequence would be (4x5)-1 = 19.

ans=102 HOW? 6,11,13,27,38,.... 6(+5),11(+7),13(+9),27(+11),38(+13),51(+15),66(+17),83(+19),102adding 5 to 6 gives 11 adding 7(two greater than previous one) gives 13...and so on... to find the nth term N squared +2

(2n-1)(-1)n

Double it minus the previous number.

It is: nth term = 29-7n

This is an arithmetic sequence which starts at 14, a = 14, and with a common difference of -1, d = -1. We can use the nth term formula an = a + (n - 1)d to get an = 14 + (n - 1)(-1) = 14 - n + 1 = 15 - n.

It is 4n -1 and so the next term will be 23

The nth term is 18 -3n and so the next term will be 3

tn = 15 - 4n (n = 1,2,3, ... )

The nth term is -7n+29 and so the next term will be -6

3n

The answer would be 120... You are increasing by odd numbers 8, 15 (difference is 7) 24 (difference of 9) 35 (difference of 11) 48 (difference of 13) 63 (difference of 15).... etc.... increasing the terms by odd numbers 7 , 9, 11, 13, 15, 17, 19, 21.. I hope this helps

The simplest, out of infinitely many possible answers, is the linear polynomial,U(n) = 4n - 1 for n = 1, 2, 3, ...